2004
DOI: 10.1614/ws-03-15r2
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination of common weed species as affected by oxygen concentration, light, and osmotic potential

Abstract: Laboratory experiments were conducted to determine the effects of oxygen concentration (21, 10, 5, and 2.5%), exposure to light, and osmotic potential on the germination of wheat, canola, and various weed species. Germination of most species increased as osmotic potential was increased. Seed germination for some species like barnyardgrass was inhibited by the combination of exposure to normoxic (21% oxygen) conditions and light. This combination of conditions may function as a signal to prevent soil surface ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 36 publications
2
38
0
3
Order By: Relevance
“…Sementes de muitas espécies de plantas daninhas podem germinar apenas na presença de luz, enquanto outras germinam igualmente em condições de presença e ausência de luz (Opeña et al, 2014). Alguns estudos já constataram comportamento similar com espécies de Echinochloa colona, E. crusgalli e E. glabrescens, o que corrobora os resultados encontrados no presente estudo (Boyd & Acker, 2004;Chauhan & Johnson, 2011;Opeña et al, 2014).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Sementes de muitas espécies de plantas daninhas podem germinar apenas na presença de luz, enquanto outras germinam igualmente em condições de presença e ausência de luz (Opeña et al, 2014). Alguns estudos já constataram comportamento similar com espécies de Echinochloa colona, E. crusgalli e E. glabrescens, o que corrobora os resultados encontrados no presente estudo (Boyd & Acker, 2004;Chauhan & Johnson, 2011;Opeña et al, 2014).…”
Section: Resultsunclassified
“…Para sementes de capimarroz em regimes de luz/escuro, ocorreu germinação em torno de 69%; em contrapartida, na ausência da luz os valores não excederam 24% (Boyd & Acker, 2004).…”
Section: Introductionunclassified
“…Na presença de luz, a germinação foi de 91% a 97% entre os biótipos avaliados, com exceção de um que apresentou 27%. Segundo Boyd & Acker (2004), a luz proporcionou 69% de germinação em sementes de Echinochloa crusgalli, comparado a 24% de germinação no escuro.…”
Section: Resultsunclassified
“…Radicle elongation of wheat, on the other hand, was greatly inhibited in both the hypotonic (127.8 mm) and hypertonic (89.3 mm) osmotic controls when compared to di H 2 O (200.0 mm). Boyd et al (2004) [40] found that the germination percentage of canola (84%, 42%, and 15%), wheat (83%, 69%, and 40%), and wild oat (42%, 11%, and 1%) decreased with increasing solute concentration in −0.01, −0.5, and −1.00 MPa polyethylene glycol 6000 solutions, respectively. Differences in response species germination between our study and that of Boyd et al (2004) [40] could be due to the presence of soil as a germination medium in our microcosm assay.…”
Section: Discussionmentioning
confidence: 97%